Urgent Dialogues in Art Teaching - Magro, Adriana Rosely; Zanin, Larissa Fabrício; Aguiar, Maira Pego de (Farol, 2024)
The XV Capixaba Seminar on Art Teaching proposed the theme “Urgent Dialogues”, aiming to promote reflections on decolonial art teaching, thus recognizing and legitimizing intersectional educational practices in art. The event was held between the 29th and 31st of August 2023, at Cine Metrópolis and in the Auditorium of the Arts Center, at the Federal University of Espírito Santo, with the participation of more than 300 people circulating through the conferences and communications sessions. This article presents reflections on the contributions of the debates fostered by the event to educational practices in art that prioritize decolonial art teaching.